The advantages of applying the concept of rhetorical style in language-oriented Journalism Studies - Molek-Kozakowska, Katarzyna (Stylistyka, 2020)
This article begins with a delineation of the context of contemporary professional journalism, particularly its market-driven, technologically advanced and discursively diverse character. Journalism studies scholars trace media evolution with the aid of content analyses. On the other hand, linguists, including stylisticians, try to capture recent changes in media language with the use of qualitative methods, e.g., with categories derived from discourse analysis, which enable them to see how hegemonic discourses are (re)constructed in journalistic texts. This article elaborates on the category of rhetorical style and shows its applicability to the studies of various media “rhetorics.” Following a review of literature and of author’s own projects, the article illustrates possible applications of and results of the analyses with the use of rhetorical style as a functional analytical category to delimit generic, register and stylistic variations of media discourse including its subgenres (e.g. headlines).